2016
DOI: 10.5944/openpraxis.8.2.279
|View full text |Cite
|
Sign up to set email alerts
|

The Best of Two Open Worlds at the National Open University of Nigeria

Abstract: It will be wise for educational institutions, from primary to tertiary level, globally, to reflect on their position and profile with respect to the new concepts of Open Educational Resources (OER) and Massive Open Online Courses (MOOCs). Responses will be diverse of course but the potential is so manifest that many institutions probably will consider the benefits to outweigh the barriers. The National Open University of Nigeria (NOUN) has decided to combine its 'classical' openness with the new digital openne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…There is a need for HEIs to initiate dialogue with governments and accreditation bodies in African countries on how MOOCs can be utilised innovatively, perhaps as part of the recognition of prior learning (RPL), to help millions of learners gain access to further training in the form of university education. University leadership also needs to encourage staff to teach actively with open content (Agbu, 2016;Czerniewicz et al, 2017), including MOOCs. Active and constructive discussions around this topic and sharing relevant knowledge and innovations could help to widen access to higher education using MOOCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a need for HEIs to initiate dialogue with governments and accreditation bodies in African countries on how MOOCs can be utilised innovatively, perhaps as part of the recognition of prior learning (RPL), to help millions of learners gain access to further training in the form of university education. University leadership also needs to encourage staff to teach actively with open content (Agbu, 2016;Czerniewicz et al, 2017), including MOOCs. Active and constructive discussions around this topic and sharing relevant knowledge and innovations could help to widen access to higher education using MOOCs.…”
Section: Discussionmentioning
confidence: 99%
“…This theme looks at how African HEIs view the value and role of MOOCs in increasing access to higher education for the masses that cannot access it, for whatever reasons, as reported in research. Of the 15 reviewed papers in this research study, only two studies by Agbu et al (2016) and Oyo and Kalema (2014) reported on the potentiality of MOOCs' being used for access to higher education. Oyo and Kalema (2014, p. 2) firmly believe that "a good design of MOOCs could widen HE access to disadvantaged students in Africa, thereby promoting holistic economic emancipation".…”
Section: Themes 421 the Perception Of The Potentiality Of Moocs To Wi...mentioning
confidence: 95%
See 2 more Smart Citations
“…For example, HarassMap, an online crowdsourcing platform that collects incidents of sexual The three open processes, with their associated practices and key characteristics. (Agbu et al 2016).…”
Section: Openness As Praxismentioning
confidence: 99%